P4.095 Young People's Knowledge, Attitude, and Behaviour Regarding Reproductive Health in the Context of Tirana, Albania. (13th July 2013) - Subashi, A
Abstract : Background: Adolescents often lack basic reproductive health RH information, knowledge, and access to health services for RH. Many have less than favourable attitudes and do not feel comfortable to discuss RH with parents or other key adults. Objectives: To assess RH knowledge, attitude and provider preference among adolescents of age 15 to 19 years. Methods: A community-based cross-sectional study was conducted in Tirana Town, capital city of Albania from October 2012 to January 2013. A structured questionnaire was utilised to collect data from the sampled population. Adolescents aged between 15 to 19 years old were interviewed about their knowledge and attitudes regarding health services for RH. The data were entered into two different computers using SPSS for windows version 17.00. Descriptive analyses using t-test were employed to depict results. Results: The majority of adolescents knew major health services for RH and the main health service providers of RH. The major sources of information for RH were internet radio 92% and television and radio for 61% school teachers for 35.9% and parents 28% of respondents. Conclusion: The level of knowledge and attitude about health services for RH, source of information for these services and service provider centres is encouraging. However, the role of health professionals and families as the source of information for the adolescents seems to be low. This should be improved using a more integrated all stakeholders particularly adolescents' families and health professionals who have a vital role to ensure adequate knowledge and favourable attitudes for utilisation of the RH in the locality.